Tsunami-Driven Debris Motion and Loads: A Critical Review - Nistor, Ioan; Goseberg, Nils; Stolle, Jacob (Frontiers in Built Environment, 2017)
Recent natural disasters, such as the 2004 Indian Ocean and 2011 Tohoku Tsunami, exhibited the importance of tsunami resistant infrastructure in high-risk coastal areas. The failure of critical infrastructure in tsunami-stricken communities has led to a recent emphasis on extreme loading conditions associated with tsunami events. One of the critical loads identified by previous research was debris loads. Debris is defined as solid objects entrained within the inundating flows and can range from construction materials to shipping vessels. The emphasis of tsunami loading has led to recent progression in the understanding of debris loads and effects, particularly in evaluating the impact of a single debris piece on a structure. The following paper reviews state-of-the-art research in tsunami-driven debris motion and loads and identifies future directions of research into debris loads and effects to aid in the design of tsunami-resistant infrastructure.